FACTORS RELATED TO DIABETIC PERIPHERAL NEUROPATHY - SUYANTO SUYANTO (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2016)
Diabetic mellitus is a crhonic disease and have a complications. One of the complication is diabetic peripheral neuropathy. 60-70% patient with diabetic mellitus also has diabetic peripheral neuropathy. Factors that contribute of diabetic peripheral neuropathy incident are length of diabetes, ages, and poor of glucose control. This study aims to knew correlate beetwen length of diabetes with diabetic peripheral neuropathy incident.Methodology: This study used cross sectional design with 79 respondents and recruited by simple random sampling methode. Data were collected from patients with diabetic mellitus. Diabetic peripheral neuropathy was measured by diabetic neuropathy symptom (DNS) . Chi square test analysis showed no significant correlate beetwen age and length of diabetes with diabetic peripheral neuropathy incident (p value > 0.05). It can be inferred that age and length of diabetes aren’t risk factor that contributed diabetic peripheral neuropathy incident. Therefore, need more reseacrh to correlate beetwen diabetic peripheral neuropathy incident with the other factors.